2022
DOI: 10.1021/acsami.2c10562
|View full text |Cite
|
Sign up to set email alerts
|

A Polyanionic Strategy to Modify the Perovskite Grain Boundary for a Larger Switching Ratio in Flexible Woven Resistive Random-Access Memories

Abstract: The intergranular interface modification of organic–inorganic hybrid perovskites (OHP) is an important issue to regulate the flexibility, stability, and resistive switching (RS) performance of resistive random-access memories (RRAMs). A novel strategy of polymer additives for OHP intergranular interface modification is explored in this work with the polyanionic backbone to improve the distribution of cage-shaped cavity molecules at the perovskite grain boundaries. Specifically speaking, poly­(1-adamantylammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 50 publications
(78 reference statements)
0
13
0
Order By: Relevance
“…The associated placing technique necessitates a bigger V SET since the resistivity of the film grows as the PMMA concentration does as well. 37 Figure 3a−b depicts the volatility distribution of the device transition voltage after analyzing the I−V curve data from the device's numerous cycles. It has been discovered through adjusting the PMMA layer's concentration that, when it is less than 15 mg/mL, the variation of the device's transition voltage steadily reduces as the PMMA concentration rises.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The associated placing technique necessitates a bigger V SET since the resistivity of the film grows as the PMMA concentration does as well. 37 Figure 3a−b depicts the volatility distribution of the device transition voltage after analyzing the I−V curve data from the device's numerous cycles. It has been discovered through adjusting the PMMA layer's concentration that, when it is less than 15 mg/mL, the variation of the device's transition voltage steadily reduces as the PMMA concentration rises.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It might be due to the fact that PMMA functions as an interfacial barrier layer, increasing the film’s initial resistance. The associated placing technique necessitates a bigger V SET since the resistivity of the film grows as the PMMA concentration does as well …”
Section: Resultsmentioning
confidence: 99%
“…Currently, researchers use various methods to better regulate the particle size of perovskite: antisolvent treatment, 22 adjusting the precursor ratio, 23 changing the annealing temperature of the film, 24 and introducing additives. 25−27 Among them, the use of non-conductive polymers as additives to modulate the perovskite films seems to be a more effective means, 28,29 which not only act as nucleation templates to modulate the particle size and crystalline quality of perovskite by virtue of its reticular structure but also cross-link the perovskite particles to strengthen the interfacial contacts, thus enhancing the surface morphology and device performance of the films.…”
mentioning
confidence: 99%
“…Considering the effect of grain boundaries on the migration of halide ions in HP thin films, Park and Lee and Lee et al attempted to adjust the particle size to regulate the migration path of halide ions, found that the number of grain boundaries is inversely proportional to the size of perovskite particles, and increased the switching ratio of the device by significantly increasing the particle size and reducing the number of grain boundaries. Currently, researchers use various methods to better regulate the particle size of perovskite: antisolvent treatment, adjusting the precursor ratio, changing the annealing temperature of the film, and introducing additives. Among them, the use of non-conductive polymers as additives to modulate the perovskite films seems to be a more effective means, , which not only act as nucleation templates to modulate the particle size and crystalline quality of perovskite by virtue of its reticular structure but also cross-link the perovskite particles to strengthen the interfacial contacts, thus enhancing the surface morphology and device performance of the films.…”
mentioning
confidence: 99%
“…
lasers, [9] photodetectors, [10] and artificial synapses [11] due to their adjustable band gap, multilevel storage, remarkable optical absorption, long electron hole diffusion length, and dielectric polarization characteristics. [1,[12][13][14][15] Their superior photoelectronic characteristics are induced by the unique electronic characteristics of inherent defects. Especially, the movement of inherent defects plays a key role in the nonvolatile memristors.
…”
mentioning
confidence: 99%